Effect of Addition of Potassium Permanganate (KMnO4) on Shelf Life of Bananas Coated With Chitosan Based Coating - Meysyaranta, Syalistya; Effendy, Mohammad; Wardhono, Endarto Yudo (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2022)
The most popular fruit is bananas. The problem bananas face declining quality or preservation of fruit before reaching the consumers. The decline in the quality of post-harvest bananas is generally caused by shrinkage of fruit mass and ripening caused by respiration and the presence of ethylene gas. One of the ways to prevent the decrease in the quality of bananas is by coating the fruit with Chitosan-based edible film. This study aims to determine the effect of adding ethylene absorber (KMnO4) to the coating Chitosan base and the composition of the coating film with the best performance in extending the shelf life of bananas. Edible film Nano Chitosan was synthesized from Sodium tripolyphosphate (TPP) and the addition of Cellulose nanocrystal (CNC) as a stabilizer agent to form a nano-composite to improve the mechanical properties of the edible coating. The method used is to provide a coating of Chitosan, and nano Chitosan with the addition of CNC and KMnO4 applied on bananas. The analysis results showed that the composition of Chitosan-CNC-KMnO4 gave the optimum performance in decline shrinkage of bananas mass with a weight loss value of 4.87% in 5th days had the lowest sugar content value on the 5th day, which was 16%.ABSTRAKBuah yang paling digemari masyarakat salah satunya adalah Pisang. Salah satu problem terkait buah pisang adalah penurunan kualitas atau pengawetan buah pisang sebelum sampai konsumen. Penurunan kualitas buah pisang pasca panen pada umumnya disebabkan oleh penyusutan massa buah dan pematangan sebelum waktunya yang diakibatkan respirasi dan adanya gas Ethylene. Penurunan kualitas buah pisang dapat dihambat dengan melapisi buah dengan coating berbasis Chitosan. Tujuan dari penelitian untuk mengetahui pengaruh penambahan Ethylene absorber (KMnO4)  pada coating film berbasiskan Chitosan serta komposisi coating film dengan performa terbaik dalam memperpanjang umur simpan buah pisang. Edible film Chitosan dan nano Chitosan disintesis dari Natrium Tripolyphospate (TPP) serta penambahan Celulose Nano Crystal (CNC) sebagai agen stabilizer sehingga terjadi keadaaan nano-komposit untuk meningkatkan properti mekanis dari edible coating. Metode yang digunakan dengan memberikan coating berbasis Chitosan dan berbasis nano Chitosan dengan penambahan CNC dan KMnO4 pada buah pisang. Hasil analisa menunjukkan bahwa coating dengan komposisi nano Chitosan-CNC-KMnO4 memberikan performa terbaik dalam menghambat penyusutan buah pisang dengan nilai susut bobot 4,87% Dan juga dalam menghambat pematangan, buah pisang memiliki nilai kadar gula terendah, yaitu sebesar 16%.